Impact of Telecommunication Protocols anent the Sustainable Development Goals: in Engineering Domain - M., B.Murshid (International Journal of Psychosocial Rehabilitation, 2020)
The elements are getting connected into the political economy at the wittiness of the whole globalization, whose vastness of the cyberspace is felt, whereby having a myriad health, economic, political, and cultural effects. Telecommunication has positive alchemy along the line of the best upbeat. Howbeit, the full comprehension is yet to be surprised. In that, telecommunication must not be endangered, but rather we must have it towards the United Nations Sustainable Development Goals (UN-SDG). The insignificant actions should not ascribe to telecommunication management. The rudimentary actions must stand to act for all sorts of communication. New developments use the sustainable development goals in lure of the good in the community's happiness. The inimitableness would be so pungent not in telecommunication. The nonpareil situation can also be there. The rapidity of evolution can hamper the development of another as well. The nuanced ideas are overlooked at the expense of technologies in tele + communication viz-a-viz social the-enigmatic states of the affair plus, thereby its consequences. Some do not address the internet.